Three-Year Outcomes in Kidney Transplant Patients Randomized to Steroid-Free Immunosuppression or Steroid Withdrawal, with Enteric-Coated Mycophenolate Sodium and Cyclosporine: The Infinity Study. (4th March 2014) - Thierry, A.; Mourad, G.; Büchler, M.; Choukroun, G.; Toupance, O.; Kamar, N.; Villemain, F.; Le Meur, Y.; Legendre, C.; Merville, P.; Kessler, M.; Heng, A.-E.; et al.
Abstract : In a six-month, multicenter, open-label trial, de novo kidney transplant recipients at low immunological risk were randomized to steroid avoidance or steroid withdrawal with IL-2 receptor antibody (IL-2RA) induction, enteric-coated mycophenolate sodium (EC-MPS: 2160 mg/day to week 6, 1440 mg/day thereafter), and cyclosporine. Results from a 30-month observational follow-up study are presented. Of 166 patients who completed the core study on treatment, 131 entered the follow-up study (70 steroid avoidance, 61 steroid withdrawal). The primary efficacy endpoint of treatment failure (clinical biopsy-proven acute rejection (BPAR) graft loss, death, or loss to follow-up) occurred in 21.4% (95% CI 11.8–31.0%) of steroid avoidance patients and 16.4% (95% CI 7.1–25.7%) of steroid withdrawal patients by month 36 (P = 0.46 ). BPAR had occurred in 20.0% and 11.5%, respectively (P = 0.19 ). The incidence of adverse events with a suspected relation to steroids during months 6–36 was 22.9% versus 37.1% (P = 0.062 ). By month 36, 32.4% and 51.7% of patients in the steroid avoidance and steroid withdrawal groups, respectively, were receiving oral steroids. In conclusion, IL-2RA induction with early intensified EC-MPS dosing and CNI therapy in de novo kidney transplant patients at low immunological risk may achieve similar three-year efficacy regardless of whether oral steroids are withheld for at least three months.